Use and assessment of the economic value of traditional medicinal plants by the Soputan Dayak tribe, East Kalimantan Province, Indonesia - RUJEHAN RUJEHAN; SETIAWATI SETIAWATI; PAULUS MATIUS; ROCHADI KRISTININGRUM; YULIANA OKTAVIA HALU (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Rujehan, Setiawati, Matius P, Kristiningrum R, Halu YO. 2024. Use and assessment of the economic value of traditional medicinal plants by the Soputan Dayak tribe, East Kalimantan Province, Indonesia. Biodiversitas 25: 2393-2403. The Soputan Dayak tribe, who live in Long Penaneh III, Long Apari Sub-district, East Kalimantan, apparently still adhere to local wisdom values in using plants as medicine and contributing to the household economy. This study aims to identify the local wisdom of the Soputan Dayak tribe in using medicinal plants and determine the economic value of medicinal plant use. Using a snowball sampling technique, the methods used were observation and direct interviews with 15 households. The data were analyzed descriptively and qualitatively using logical explanation through a substitute-market approach to determine economic value. The results showed that the use of medicinal plants in the village of Long Penaneh III covered 41 families of 64 species with various benefits. The most used plant organs were leaves (50%) and roots (24%), with the rest comprising tubers, stems, fruit, shoots, skins, flowers, and cambium. The main diseases treated with medicinal plants were back pain (17%), cholesterol (14%), high blood pressure and leukorrhea (12% each), and flu, fever, hypoglycemia, ulcers, and kidney concerns (9% each). The economic value assessment from the 64 species showed IDR 36,685,000 per year could be obtained, based on the information of 15 respondents, with an average per household of IDR 2,445,666.67 per year. The economic value obtained is sufficient to support the household economy.